THE EFFECT OF COMPENSATION ON PERFORMANCE THROUGH EMPLOYEE'S WORK MOTIVATION AT PT. SKV PROSPEROUS SURABAYA - Mulyani, Sri; Utari, Woro (JURNAL EKBIS, 2023)
In order to improve the company's performance, various efforts are needed to improve employee performance so that it fits the company's needs in dealing with current developments, so the purpose of this study is to describe the compensation, motivation and performance of employees of PT. SKV Prosperous Surabaya, to test and analyze the effect of compensation on performance through work motivation of employees of PT. SKV Prosperous Surabaya. This research is an explanatory research with a quantitative approach. The population uses all employees of PT. SKV Prosperous Surabaya, totaling 50 people who are also the research sample because it uses a saturated sampling technique. The hypothesis testing method used in this study is Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that employee performance, employee motivation and compensation given to employees at PT. SKV Prosperous Surabaya is already in high condition. Compensation has a significant effect on work motivation. Compensation has a significant effect on employee performance. Work motivation has a significant effect on employee performance. Compensation has a significant effect on employee performance mediated by work motivation at PT. SKV Prosperous Surabaya